2012
DOI: 10.1016/j.neurobiolaging.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Regional changes in type 1 cannabinoid receptor availability in Parkinson's disease in vivo

Abstract: The type 1 cannabinoid receptor (CB1) is a crucial modulator of synaptic transmission in brain and has been proposed as a potential therapeutic target in Parkinson's disease (PD), especially for treatment of levodopa-induced dyskinesias (LID). Our aim was to measure CB1 levels in brains of PD patients in vivo and to investigate the relation between CB1 availability and LID. We studied 12 healthy controls and 29 PD patients (9 drug-naïve patients with early PD, 10 patients with advanced PD and LID, and 10 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 42 publications
4
70
0
2
Order By: Relevance
“…18 F]MK-9470 has shown significant decreases in CB1R levels in the substantia nigra of early de novo and advanced PD patients with and without LIDs (van Laere et al, 2012). However, no differences were found in regional CB1R availability between advanced PD patients with and without LIDs and regional CB1R levels were not associated with LIDs severity (van Laere et al, 2012).…”
Section: Cannabinoidmentioning
confidence: 99%
“…18 F]MK-9470 has shown significant decreases in CB1R levels in the substantia nigra of early de novo and advanced PD patients with and without LIDs (van Laere et al, 2012). However, no differences were found in regional CB1R availability between advanced PD patients with and without LIDs and regional CB1R levels were not associated with LIDs severity (van Laere et al, 2012).…”
Section: Cannabinoidmentioning
confidence: 99%
“…A PET study using [ 18 F]MK-9470 has shown significant decreases in CB1R levels in the substantia nigra of early de novo and advanced PD patients with and without LIDs (van Laere et al, 2012). However, no differences were found in regional CB1R availability between advanced PD patients with and without LIDs and regional CB1R levels were not associated with LIDs severity (van Laere et al, 2012). Further studies using higher selective CB1R PET radioligands are needed in order to further elucidate the role of these receptors in the pathophysiology of PD.…”
Section: Cannabinoidmentioning
confidence: 99%
“…CB 1 receptor binding is increased in PD patients and 1-methyl-4-phenyl-1,2,3,6-tetra hydropyridine (MPTP)-treated marmosets at caudate-putamen level [17] while a decrease in CB 1 receptor availability has been observed in the SN of PD patients [18]. The eCB system undergoes a drastic remodeling during the course of PD pathogenesis.…”
Section: The Ecb Signaling System: Control Of Motor Behavior and Neurmentioning
confidence: 99%
“…Since there are no CB 1 receptors on DAergic neurons, the effects on DAergic transmission are indirectly mediated by CB 1 -containing GABAergic and glutamatergic neurons. This may help to understand why the eCB system results overactivated in PD as consequence of the loss of DAergic innervation and facilitation of DA-evoked motor behavior [18,23].…”
Section: The Ecb Signaling System: Control Of Motor Behavior and Neurmentioning
confidence: 99%